Non‐invasive prenatal testing offered as part of a combined first‐trimester screening program identifies tetrasomy 18p in a high‐risk pregnancy. (10th November 2016) - Lildballe, Dorte Launholt; Vogel, Ida; Lund, Ida Charlotte Bay; Stornes, Inger; Jørgensen, Mette Warming; Vestergaard, Else Marie
Abstract : What's already known about this topic? Basic NIPT is a sensitive method that may reveal unexpected structural chromosomal abnormalities What does this study adds? The case illustrates the importance of choosing the right sample (chorionic villi or amniotic fluid) and analytical method e.g. QF‐PCR or arrayCGH for confirmative analysis after an abnormal NIPT result.